A PROSE FICTION THEORY OF JAVANESE LITERATURE BASED ON FOLKTALES - Soedjijono, Soedjijono; Susilo, Edy (ATAVISME, 2014)
his study aims to build the theory of prose fiction of Javanese literature based on the study of folktale as a first step towards the development of the study of native literature. This study?s objects are ten pieces of folktale, consisting of 93 story?s episodes, which were published in Panjebar Semangat magazine between 2006-2010. This study uses structural?phenomenological-hermeneutic approach, by applying phenomenological reduction, eidetic reduction, and transcendental reduction. The results of phenomenological reduction are nine elements of the work: author, a title of the story, special object, language, setting, character, emotional event, plot, and idea. The results of eidetic reduction are opposition rule, internal relation rule, and external relation rule. The results of transcendental reduction are the values of holiness, truth, and kindness. his study aims to build the theory of prose fiction of Javanese literature based on the study of folktale as a first step towards the development of the study of native literature. This study?s objects are ten pieces of folktale, consisting of 93 story?s episodes, which were published in Panjebar Semangat magazine between 2006-2010. This study uses structural?phenomenological?hermeneutic approach, by applying phenomenological reduction, eidetic reduction, and transcendental reduction. The results of phenomenological reduction are nine elements of the work: author, a title of a story, special object, language, setting, character, emotional event, plot, and idea. The results of eidetic reduction are opposition rule, internal relation rule, and external relation rule. The results of transcendental reduction are the values of holiness, truth, and kindness. Abstrak: Penelitian ini bertujuan untuk membangun teori prosa fiksi sastra Jawa berbasis pada kajian cerita rakyat sebagai langkah pertama menuju pengembangan studi sastra kepribumian. Penelitian ini menggunakan objek kajian sepuluh buah cerita rakyat, terdiri atas 93 episode cerita, yang dimuat di majalah Panjebar Semangat antara tahun 2006-2010. Penelitian ini menggunakan pendekatan analisis struktura?fenomenologis-hermeneutik, dengan menerapkan reduksi fenomenologis, reduksi eidetis, dan reduksi transendental. Hasil dari reduksi fenomenologis adalah sembilan unsur karya: pengarang, judul cerita, objek khusus, bahasa, latar cerita, tokoh cerita, peristiwa emosional, alur cerita, dan gagasan. Hasil dari reduksi eidetis adalah kaidah oposisi, kaidah relasi internal, dan kaidah relasi eksternal. Hasil dari reduksi transendental adalah nilai kekudusan, nilai kebenaran, dan nilai kebaikan. Kata-Kata Kunci: teori prosa fiksi sastra Jawa; cerita rakyat; pendekatan struktural-fenomeno logis-hermeneutik